(untitled) (Bangladesh Journal of Physics, 2022)
The biological effectiveness of laser driven protons on cells in a single exposure has been studied. In this experiment, V79 cell lines were irradiated with laser driven protons whereas comparison with the effectiveness of X-ray exposures was studied. Here design of the experiment and irradiation setup are explained in details as it is a first and foremost experiment in this field. Bangladesh Journal of Physics, 27(2), 59-70, December 2020